Inventory Of Gastropods In The Coastal Area Of Desa Sungai Nibung West Kalimantan - Safitri, Ikha; Kushadiwijayanto, Arie Antasari; Sofiana, Mega Sari Juane; Apriansyah, Apriansyah; Nurrahman, Yusuf Arief; Nurdiansyah, Syarif Irwan; Enjella, Enjella; Ginting, Madi Juna Permalem (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
Desa Sungai Nibung is a village located in Teluk Pakedai District, Kubu Raya Regency, West Kalimantan. This village is one of the conservation areas established by the Regional Government of West Kalimantan Province in 2020. Desa Sungai Nibung has a high diversity of natural resources, one of which is gastropods. Gastropods are organisms that act as grazers, scavengers, and predators. These organisms can live in waters, coastal and terrestrial. Its diversity has been reported to be more than 75,000 species. Several gastropods have been used by the local community as food with a high protein source. Gastropods found on the coast of Sungai Nibung Village are Ellobium, Cassidula, Nerita, Neritina, Chicoreus, Cerithidea, Littoria, Potamopyrgus, and Onchidium.